Income inequality not gender inequality positively covaries with female sexualization on social media - Blake, Khandis R. (Proc Natl Acad Sci U S A, 2018)
Publicly displayed, sexualized depictions of women have proliferated, enabled by new communication technologies, including the internet and mobile devices. These depictions are often claimed to be outcomes of a culture of gender inequality and female oppression, but, paradoxically, recent rises in sexualization are most notable in societies that have made strong progress toward gender parity. Few empirical tests of the relation between gender inequality and sexualization exist, and there are even fewer tests of alternative hypotheses. We examined aggregate patterns in 68,562 sexualized self-portrait photographs (“sexy selfies”) shared publicly on Twitter and Instagram and their association with city-, county-, and cross-national indicators of gender inequality. We then investigated the association between sexy-selfie prevalence and income inequality, positing that sexualization—a marker of high female competition—is greater in environments in which incomes are unequal and people are preoccupied with relative social standing. Among 5,567 US cities and 1,622 US counties, areas with relatively more sexy selfies were more economically unequal but not more gender oppressive. A complementary pattern emerged cross-nationally (113 nations): Income inequality positively covaried with sexy-selfie prevalence, particularly within more developed nations. To externally validate our findings, we investigated and confirmed that economically unequal (but not gender-oppressive) areas in the United States also had greater aggregate sales in goods and services related to female physical appearance enhancement (beauty salons and women’s clothing). Here, we provide an empirical understanding of what female sexualization reflects in societies and why it proliferates.